THE ROLE OF TECHNOLOGY IN APPLIED LINGUISTICS RESEARCH: OPPORTUNITIES AND CHALLENGES - Wirentake, Wirentake (Transpublika Publisher, 2022)
This study explores the role of technology in applied linguistics research, focusing on both the opportunities and challenges it presents. Employing a descriptive qualitative approach combined with a comprehensive literature review, the research provides an in-depth analysis of how technological advancements, particularly artificial intelligence and machine learning, are shaping language learning and research. The study identifies key themes, including the potential benefits of technology in personalizing language education and the ethical concerns related to data privacy and algorithmic bias. Additionally, it highlights the digital divide and the need for continuous teacher training to effectively integrate these tools into educational contexts. The findings emphasize the importance of balancing technological innovation with the preservation of the human element in language learning, ensuring that technological integration is both effective and equitable.